Osmo and ionic regulation of black tiger prawn (Penaeus monodon Fabricius 1798) juveniles exposed to K+ deficient inland saline water at different salinities - Tantulo, Uras; Fotedar, Ravi (Elsevier, 2007)
An 11-day trial was conducted to investigate the osmoregulatory capacity (OC) and regulation of K+, Na+, Ca2+ and Mg2+ of Penaeus monodon juveniles when exposed to K+ deficient inland saline water (ISW) of four different salinities (5, 15, 25 and 35 ppt). The survival of juveniles showed a positive linear relationship (R2 ranging from 0.72 to 0.98) with salinity. At the end of the trial, juveniles were able to survive only in 5 ppt of ISW and showed no changes in OC when transferred from ocean water (OW) to ISW. Further, the OC of juveniles in 5 ppt of ISW was significantly different (P < 0.05) from the OC of juveniles exposed to 15, 25 and 35 ppt and exhibited strong serum K+, Na+, Ca2+ and Mg2+ regulation monitored over 16 h. In contrast, at 35 ppt, significant decrease (P < 0.05) in serum K+ and Mg2+ concentrations and accumulation of serum Na+ concentration occurred after 16 h of exposure to ISW. At higher salinity, an increase in serum Na+ concentration leads to an increase in the serum osmolality of the juveniles, which in turn causes decrease in the OC of the juveniles. The results of this study suggest that K+ deficiency in ISW has a negative effect on survival, OC and the ability of P. monodon juveniles to regulate serum Na+, K+, Ca2+ and Mg2+ concentrations. These effects are compounded as salinity increases.